Impact of the expert consensus on polypharmacy and potentially inappropriate medication use in elderly lung cancer outpatients with multimorbidity: An interrupted time series analysis, 2016–2021 - Tian, Fangyuan; Chen, Zhaoyan; Tang, Rui; Feng, Qiyi; Wu, Fengbo (Frontiers in Pharmacology, 2022)
Objectives: Elderly lung cancer patients often have chronic diseases other than lung cancer. Therefore, this kind of population is often accompanied by polypharmacy. This situation and the resulting potentially inappropriate medication (PIM) use are an increasing global concern. In this context, the Chinese Association of Geriatric Research issued an expert consensus on the safety management of polypharmacy. However, the long- and short-term effects of the expert consensus on polypharmacy and PIM use are not clear. Methods: The study was conducted in Chengdu, a city in southwestern China, consisting of prescriptions for elderly lung cancer outpatients with multimorbidity (cancer with other diseases) from January 2016 to December 2021. The 2019 Beers criteria were used to evaluate PIM use, and interrupted time series analysis was used to evaluate the longitudinal effectiveness of expert consensus by measuring the prevalence of polypharmacy and PIM use. We used R software version 4.2.0 for data analysis. Results: A total of 7,238 elderly lung cancer outpatient prescriptions were included in the study. After the publication of the expert consensus, the level (β = -10.273, P ＜ 0.001) of the prevalence of polypharmacy decreased, but the trend (β = 0.158, P = 0.855) of polypharmacy increased. The prevalence of PIM use decreased abruptly (β = -22.828, P < 0.001) after the intervention, but the long-term trend was still upward (β = 0.907, P = 0.916). Conclusion: The long-term effects of the publication of the expert consensus on the prevalence of polypharmacy and PIM use in hospitals in Chengdu were not optimal. Future research on interventions rationing polypharmacy and PIM use is needed.